Automated Assay of Telomere Length Measurement and Informatics for 100, 000 Subjects in the Genetic Epidemiology Research on Adult Health and Aging (GERA) Cohort. Issue 4 (19th June 2015) - Lapham, Kyle; Kvale, Mark N; Lin, Jue; Connell, Sheryl; Croen, Lisa A; Dispensa, Brad P; Fang, Lynn; Hesselson, Stephanie; Hoffmann, Thomas J; Iribarren, Carlos; Jorgenson, Eric; Kushi, Lawrence H; et al.
Abstract: The Kaiser Permanente Research Program on Genes, Environment, and Health (RPGEH) Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort includes DNA specimens extracted from saliva samples of 110, 266 individuals. Because of its relationship to aging, telomere length measurement was considered an important biomarker to develop on these subjects. To assay relative telomere length (TL) on this large cohort over a short time period, we created a novel high throughput robotic system for TL analysis and informatics. Samples were run in triplicate, along with control samples, in a randomized design. As part of quality control, we determined the within-sample variability and employed thresholds for the elimination of outlying measurements. Of 106, 902 samples assayed, 105, 539 (98.7%) passed all quality control (QC) measures. As expected, TL in general showed a decline with age and a sex difference. While telomeres showed a negative correlation with age up to 75 years, in those older than 75 years, age positively correlated with longer telomeres, indicative of an association of longer telomeres with more years of survival in those older than 75. Furthermore, while females in general had longer telomeres than males, this difference was significant only for those older than age 50. An additional novel finding was that the variance of TL between individuals increased with age. This study establishes reliable assay and analysis methodologies for measurement of TL in large, population-based human studies. The GERA cohort represents the largest currently available such resource, linked to comprehensive electronic health and genotype data for analysis.